Heparan Sulfate: A Ubiquitous Glycosaminoglycan with Multiple Roles in Immunity - Simon Davis, David Anak; Parish, Christopher R. (Frontiers in Immunology, 2013)
Heparan sulfate (HS) is a highly acidic linear polysaccharide with a very variable structure. It is ubiquitously expressed on cell surfaces and in the extracellular matrix (ECM) and basement membrane (BM) of mammalian tissues. Synthesised attached to various core-proteins to form HS-proteoglycans (HSPG), HS is capable of interacting with various polypeptides and exerting diverse functions. In fact, a bioinformatics analysis of mammalian proteins that express a heparin/HS binding motif and are associated with the immune system identified 235 candidate proteins, the majority having an intracellular location. This simple analysis suggests that HS may, in fact, interact with many more components of the immune system than previously realised. Numerous studies have also directly demonstrated that HS plays multiple prominent functional roles in the immune system that are briefly reviewed in this article. In particular, the molecule has been shown to regulate leukocyte development, leukocyte migration, immune activation and inflammatory processes.